2017
DOI: 10.1186/s13054-017-1745-7
|View full text |Cite
|
Sign up to set email alerts
|

Low-volume resuscitation with normal saline is associated with microvascular endothelial dysfunction after hemorrhage in rats, compared to colloids and balanced crystalloids

Abstract: BackgroundRestoration of endothelial glycocalyx (EG) barrier may be an essential therapeutic target for successful resuscitation. The aim of this study was to compare in vivo the effects of resuscitation with normal saline (NS) to lactated Ringer’s solution (LR), 5% albumin and fresh frozen plasma (FFP) on their ability to maintain EG and barrier function integrity, mitigate endothelial injury and inflammation, and restore vascular homeostasis after hemorrhagic shock.MethodsAnesthetized rats (N = 36) were subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
72
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 55 publications
3
72
2
1
Order By: Relevance
“…This is considered to be a reliable method of measuring GCX thickness in vivo. We observed that GCX index was significantly lower in only group NS than in group C, and there were no significant differences in group NS-A and NS-V compared to group C. Consistent with the observed results for GCX thickness, the plasma concentration of syndecan-1 was significantly higher in group NS than in group C, indicating that fluid resuscitation using only normal saline leads to GCX damage [11], resulting in a poor prognosis [23][24][25].…”
Section: Discussionsupporting
confidence: 83%
“…This is considered to be a reliable method of measuring GCX thickness in vivo. We observed that GCX index was significantly lower in only group NS than in group C, and there were no significant differences in group NS-A and NS-V compared to group C. Consistent with the observed results for GCX thickness, the plasma concentration of syndecan-1 was significantly higher in group NS than in group C, indicating that fluid resuscitation using only normal saline leads to GCX damage [11], resulting in a poor prognosis [23][24][25].…”
Section: Discussionsupporting
confidence: 83%
“…However, we would not anticipate other proteins to significantly participate in barrier integrity and/or not be present in human plasma in sufficient quantities to provide protection. The exception to this could be albumin, as it has been reported to provide protection to the endothelium in a rodent model of hemorrhage (30). As this study represents our initial findings into the key role of fibrinogen as an endothelial protector, future studies are needed to define the precise mechanisms for this protection.…”
Section: Discussionmentioning
confidence: 92%
“…Previously, we reported that H 2 inhalation upon induction of HS enhanced tolerance to blood loss and hemodynamic stability after fluid resuscitation with four times the shed blood volume of normal saline ( 24 ). However, that experimental protocol was inconsistent with typical clinical scenarios and the high infusion volume was harmful ( 33 , 34 ). Therefore, in this study H 2 inhalation was started after shock, mimicking H 2 inhalation in an ambulance.…”
Section: Discussionmentioning
confidence: 99%